5-Mercaptotetrazolyl-derived metallaboratranes. Issue 7 (28th January 2019) - Hill, Anthony F.; Schwich, Torsten; Xiong, Yaoyao
Abstract : The salts Na[H2 B(tt t Bu )2 ] and Na[HB(tt t Bu )3 ] (tt t Bu = 1-tert.butyl-5-thiotetrazole have been used to provide the new metallaboratranes [Ru(CO)(PPh3 ){κ 4 - B, S, S ′, S ′′-B(tt t Bu )3 }], [IrH(CO)(PPh3 ){κ 3 - B, S, S ′-BH(tt t Bu )2 }] and [Ru(CO)(PPh3 )2 {κ 3 - B, S, S ′-BH(tt t Bu )2 }]. Abstract : The reactions of 1- tert butyl-5-thiotetrazole (Htt t Bu ) with Na[BH4 ] provides Na[H2 B(tt t Bu )2 ] (Na[1 ]) or Na[HB(tt t Bu )3 ] (Na[2 ]) in refluxing THF or xylene, respectively. Treating [RuCl(Ph)(CO)(PPh3 )2 ] with Na[2 ] affords the triply-buttressed ruthenaboratrane [Ru(CO)(PPh3 ){κ 4 - B, S, S ′, S ′′-B(tt t Bu )3 }] (5 ) whilst Na[1 ] with [IrCl(CO)(PPh3 )2 ] or [RuCl(Ph)(CO)(PPh3 )2 ] provides rare examples of doubly-buttressed metallaboratranes [IrH(CO)(PPh3 ){κ 3 - B, S, S ′-BH(tt t Bu )2 }] (7 ) and [Ru(CO)(PPh3 )2 {κ 3 - B, S, S ′-BH(tt t Bu )2 }] (12 ), the latter via the isolable thiotetrazoylborate complex [Ru(Ph)(CO)(PPh3 ){κ 3 - H, S, S ′-H2 B(tt t Bu )2 }] (11 ).